Analisis Perbandingan Pengunaan Kendaraan Bermotor dan Kendaraan Motor Listrik di Wilayah Soloraya Tahun 2024 (Studi Kasus: Surakarta dan sukoharjo) - Badu, Muswarjodin; Sodikin, Sodikin; Ristanto, Iwan (Jurnal Talenta Sipil, 2025)
Transport, derived from the Latin word "transportare" (with "trans" meaning "across" or "beyond" and "portare" meaning "to carry" or "to bear"), is defined as the process and activity of moving goods or passengers from one place to another. This study aims to analyze the comparison between gasoline-powered vehicles and electric motorcycles in the Soloraya region for the year 2024. A quantitative approach based on statistical information was employed. To address the research problem, precise measurement of the values of the objects under study was performed using surveys, interviews, and questionnaires. The data collected were processed to obtain results regarding the usage of electric motorcycles versus gasoline-powered motorcycles in the Soloraya region. The study found that satisfaction levels and preferences were similar among users of both electric and conventional motorcycles. However, conventional motorcycle users expressed a desire to replace their vehicles within the next 1-2 years. The main reason for choosing electric motorcycles was their environmental friendliness, while conventional motorcycle users cited operational cost as their primary reason. The study concluded that, in terms of range, electric motorcycles have an average distance of 10 km, while conventional motorcycles can cover 11-20 km. Additionally, electric motorcycle users typically use their vehicles 5-6 days a week, whereas conventional motorcycle users tend to use theirs weekly.